1994
DOI: 10.1366/0003702944028551
|View full text |Cite
|
Sign up to set email alerts
|

XeCl Excimer Laser-Induced Shock Wave Plasma and its Application to Emission Spectrochemical Analysis

Abstract: A XeCl excimer laser (20 ns, 15–70 mJ) has been focused on a Zn plate in surrounding gas at low pressures (100–1500 Pa). The characteristics of the resultant plasma are examined with the use of a unique time-resolved spectroscopic method. A density jump in the distribution of Zn atoms is clearly observed, which indicates the generation of a shock wave. Furthermore, it is proved that the relationships among the displacement length of the front of the emission of the Zn neutral emission line, the pressure of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
57
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(66 citation statements)
references
References 14 publications
9
57
0
Order By: Relevance
“…[3][4][5][6][7] We reported on LIP images of copper emission lines with spatially-resolved spectrometric techniques by using a two-dimensional imaging spectrometer 3 or interference filters, 8 which yielded information on the overall variations of the plasma expansion. However, these spatiallyresolved measurements cannot be employed for spectrochemical analysis, because they provide only the emission image at a A time-resolved spectrometric measurement was conducted to determine temporal variations in the excitation temperature within a single laser plume caused by a Nd:YAG laser plasma.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] We reported on LIP images of copper emission lines with spatially-resolved spectrometric techniques by using a two-dimensional imaging spectrometer 3 or interference filters, 8 which yielded information on the overall variations of the plasma expansion. However, these spatiallyresolved measurements cannot be employed for spectrochemical analysis, because they provide only the emission image at a A time-resolved spectrometric measurement was conducted to determine temporal variations in the excitation temperature within a single laser plume caused by a Nd:YAG laser plasma.…”
Section: Introductionmentioning
confidence: 99%
“…This effect should be noticed when a sample comprising elements having different thermal properties is analyzed by LIPS. Kagawa et al 4,13,14) also reported that the selective vaporization negligibly take place when UV laser with a short pulse duration is focused on a target at reduced pressure.…”
Section: Resultsmentioning
confidence: 99%
“…LIPS under evacuated pressures further can yield better analytical performance because of the low fluctuation of the emission intensity as well as the large signal to background ratio. [1][2][3][4][5][6][7] However, selective vaporization of sample atoms often cause serious problem during the laser ablation process, so that the analytical result involves large errors. Selective vaporization was observed by Baldwin 8) and Russo 9) in laser atomization on brass.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In LIPS, low-pressure laser-induced plasmas (LP-LIP) have favorable features such as a relatively low fluctuation of the emission intensity, as well as a high signal-to-background ratio. [2][3][4][5][6][7][8] In LIPS under atmospheric pressures, electron collision 9 and electron-ion recombination 10 are considered to be the dominant excitation mechanisms of sample atoms. Especially in LP-LIP, excitation by a shock wave 5,11,12 and collisions with metastable states of noble gases 11,13,14 are considered to be effective excitation mechanisms of sample atoms in addition to the above-mentioned mechanisms.…”
Section: Introductionmentioning
confidence: 99%